Evaluasi Program Pekarangan Pangan Lestari (P2L) untuk Mewujudkan Ketahanan Pangan Rumah Tangga di Kota Padang - Dian Hafizah; Ismi Padilah; Nuraini Budi Astuti (Jurnal Ilmu Pertanian Indonesia, 2024)
The purposes of research are to describe the implementation of the Sustainable Food Crop Program and evaluate the activities of the Sustainable Food Crop Program in Padang City. This research method used a quantitative descriptive method with a survey research type. The samples taken were 36 people from 9 KWTs. Data were collected using a questionnaire. The results of the research show that the implementation of the Sustainable Food Yard Program (P2L) in Padang City has been conducted well in accordance with the Technical Instructions for Implementing the P2L program in 2022. For the second objective, it was evaluated using four variables, namely target accuracy, program socialization, program objectives, and program monitoring. The research results were displayed in the form of scores and it was found that the total percentage score for all variables was 94.79%. The target accuracy variable obtained a score of 37.69 with a score percentage of 94%. The program socialization variable obtained a score of 37.75 with a score percentage of 94%. The program objective variable obtained a score of 36.22 with a score percentage of 91% and the program monitoring variable obtained a score of 16.00 with a percentage of 100%. It can be concluded that the Food Yard Program (P2L) in Padang City has been conducted effectively. Keywords: budikdamber, effectiveness, food security, sustainable food crop (P2L)